Blautia and Prevotella sequences distinguish human and animal fecal pollution in Brazil surface waters. Issue 6 (9th July 2014) - Koskey, Amber M.; Fisher, Jenny C.; Eren, A. Murat; Ponce‐Terashima, Rafael; Reis, Mitermayer G.; Blanton, Ronald E.; McLellan, Sandra L.
Summary Untreated sewage discharges and limited agricultural manure management practices contribute to fecal pollution in rural Brazilian waterways. Most microbial source tracking studies have focused on Bacteroidales, and few have tested host‐specific indicators in underdeveloped regions. Sequencing of sewage and human and animal feces with Illumina HiSeq revealed Prevotellaceae as the most abundant family in humans, with Lachnospiraceae and Ruminococcaceae also comprising a large proportion of the microbiome. These same families were also dominant in animals. Bacteroides, the genus containing the most commonly utilized human‐specific marker in the United States was present in very low abundance. We used oligotyping to identify Prevotella and Blautia sequences that can distinguish human fecal contamination. Thirty‐five of 61 Blautia oligotypes and 13 of 108 Prevotella oligotypes in humans were host‐specific or highly abundant (i.e. host‐preferred) compared to pig, dog, horse and cow sources. Certain human Prevotella and Blautia oligotypes increased more than an order of magnitude along a polluted river transect in rural Brazil, but traditional fecal indicator levels followed a steady or even decreasing trend. While both Prevotella and Blautia oligotypes distinguished human and animal fecal pollution in Brazil surface waters, Blautia appears to contain more discriminatory and globally applicable markers for tracking sources of fecal pollution.